Early identification of patients in need of palliative care in Slovenian general practice - Klok, Lisette (Zdravstveno varstvo, 2018)
Background: To help general practitioners (GPs) in early identification of patients with palliative care (PC) needs, this pilot study aimed to determine the potential of the combined original surprise question (SQ1) (%Would I be surprised if this patient died within the next 12 months?%) and the second surprise question (SQ2) (%Would I be surprised if this patient was still alive after 12 months?%). We hypothesized that answering these SQs would trigger them to make a multidimensional care plan. Methods: 26 Slovenian GPs, randomized into 4 groups, were invited to write a care plan for each of the four patients described in case vignettes (2 oncologic, 1 organ failure and 1 frailty case). GPs in group 1 were only asked to write a care plan for each patient. GPs in group 2 answered SQ1 and GPs in groups 3 and 4 answered SQ1 and SQ2 before writing the care plan. The type and number of PC aspects mentioned in the respective care plans were quantified into a numeric RADboud ANTicipatory (RADIANT) score. Results: Mean RADIANT scores in groups 1-4 were 2.2, 3.6, 2.5 and 3.1, respectively. When comparing the different vignettes, vignette B (terminal oncologic patient) scored best (3.6). Mean RADIANT scores in groups 3 and 4 were slightly higher for GPs who would be surprised compared to GPs who would not be surprised if the patient was still alive in 12 months. Conclusion: The combined SQs were considered helpful in the early identification of patients in need of PC in Slovenian general practice
Keywords: cancer; demenca; dementia; frail elderly; general practitioners; krhkost pri starostnikih; odpoved organov; organ failure; paliativna oskrba; palliative care; rak; Slovenia; Slovenija; splošni zdravniki; surprise question; vprašanje presenečenja